Fiscal Success During COVID-19 Says Believe the Good News - Adam S. Posen (Intereconomics)
Abstract Too much blood in terms of unemployment and sweat in terms of intellectual effort has been spent on trying to determine the amount of fiscal space that economies have — our policy focus instead should be on what to do with the fiscal space that almost all advanced economies (and a surprising number of emerging market economies) actually have.